USAHA CHIPS TORTILA INSAN MANDIRI DI DESA BENGKING, KECAMATAN JATINOM, KABUPATEN KLATEN - Sundari, Mei Tri; Mulya H, Sugiharti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
Business Tortila Chips Insan Mandiri is a business that is engaged in theprocessing of corn. At one stage in the production process, i.e. the moldingstage tortilla chips, are still done manually so it takes a long time, shapes andsizes are not uniform. IbM program was implemented with the aim to increaseefficiency in the production process, especially in terms of shortening themolding and training partners to create a simple financial reports. Service activities using the dialog metode (FGD), introduction and applicationof technology, training, and assistance in an integrated manner. Technologythat introduced and applied to partners through this IbM activity is aTortila Chips display device to create rounded shapes, rectangles and hexagons.The training are simple financial bookkeeping trainings. Introduction to Tortilla Chips display device has been done and partnershave used these tools properly, so the shorter the time required, the productioncapacity can be increased, the product has a uniform shape and size so that thequantity and quality becomes better, which in turn will increase profits. Bookkeepingtraininghasalsobeenimplementedsothatpartnersareabletocreateasimplefinancialreportindependently